A systematic review of school-based sexual health interventions to prevent STI/HIV in sub-Saharan Africa - Poobalan Amudha; Paul-Ebhohimhen Virginia A; van Teijlingen Edwin R (BMC, 2008)
Abstract Background The HIV/AIDS epidemic remains of global significance and there is a need to target (a) the adolescent age-groups in which most new infections occur; and (b) sub-Saharan Africa where the greatest burden of the epidemic lies. A focused systematic review of school-based sexual health interventions in sub-Saharan Africa to prevent HIV/AIDS and Sexually Transmitted Infections (STI) in this age group was therefore conducted. Methods Searches were conducted in Medline, Embase, Cinahl and PsychINFO according to agreed a priori criteria for studies published between 1986 and 2006. Further searches were conducted in UNAIDS and WHO (World Health Organization) websites, and 'Google'. Relevant journals were hand-searched and references cited in identified articles were followed up. Data extraction and quality assessment was carried out on studies selected for full text appraisal, and results were analysed and presented in narrative format. Results Some 1,020 possible titles and abstracts were found, 23 full text articles were critically appraised, and 12 articles (10 studies) reviewed, reflecting the paucity of published studies conducted relative to the magnitude of the HIV epidemic in sub-Saharan Africa. Knowledge and attitude-related outcomes were the most associated with statistically significant change. Behavioural intentions were more difficult to change and actual behaviour change was least likely to occur. Behaviour change in favour of abstinence and condom use appeared to be greatly influenced by pre-intervention sexual history. Conclusion There is a great need in sub-Saharan Africa for well-evaluated and effective school-based sexual health interventions.